To calculate the kinetic energy (KE) of the student and her bicycle, we can use the formula:
\[ KE = \frac{1}{2} m v^2 \]
where:
- \( m \) is the mass (in kilograms),
- \( v \) is the velocity (in meters per second).
Given:
- \( m = 56 \) kg
- \( v = 11 \) m/s
Now, substituting in the values:
\[ KE = \frac{1}{2} \times 56 , \text{kg} \times (11 , \text{m/s})^2 \]
Calculating \( (11 , \text{m/s})^2 \):
\[ (11 , \text{m/s})^2 = 121 , \text{m}^2/\text{s}^2 \]
Now substituting back into the kinetic energy formula:
\[ KE = \frac{1}{2} \times 56 , \text{kg} \times 121 , \text{m}^2/\text{s}^2 \]
Calculating \( \frac{1}{2} \times 56 = 28 \):
\[ KE = 28 , \text{kg} \times 121 , \text{m}^2/\text{s}^2 \]
Now, calculating \( 28 \times 121 \):
\[ 28 \times 121 = 3388 , \text{J} \]
Thus, the kinetic energy of the student and her bicycle is:
\[ \boxed{3,388 , \text{J}} \]